Impacts of natural and artificial diet on growth and survival rate oreochromis niloticus / Ahmad Faiz Mansor - Mansor, Ahmad Faiz (Faculty of Applied Sciences, 2014)
A 56 days long experiment was conducted with a view and objective to observe the impacts of natural and artificial diet on Oreochromis niloticus to provide the data for future research and help farmer to improve their farming of O. niloticus species in order to boost up their production. There were two treatment in this experiment which is Tank A and Tank B. Each of the tanks was stocked with 20 fry having an initial weight 1.58 ± 0.05 g and 1.67 ± 0.65 g and initial total length 4.90 ± 0.17 cm and 4.86 ± 0.20 cm respectively in a cistern of (57 x 38 x 40) cm plastic tank. The fry fed with an artificial diet showed a significantly different better result in term of weight gained, length of the fish, head length, length of dorsal fin, pectoral fin length, length of aral fin base and the standard length of the fish. Both of the diet shown a 100% of survival rate.